Caracterização da cianobactéria Rhabdoderma lineare: uma abordagem fisiológica, bioquímica e metabólica - Valdez, Nicolas Ignacio (Universidade Federal de São Carlos, 2022)
Cyanobacteria are a group of single-celled, prokaryote and photosynthetic organisms. It has an enormous morphological, physiological and metabolic diversity and this allows the application of these organisms in several areas. This work aimed to characterize the biomass of the cyanobacterium Rhabdoderma lineare (3083) in relation to its growth, photosynthetic physiology, biochemical composition, secondary metabolites and toxicity, evaluating its biotechnological potential and possible commercial applications. To evaluate the growth, 3 photobioreactors with different optical paths were tested, namely, Erlenmeyer, cylindrical bioreactor and tissue culture flask, however, the use of optimal light intensity during the cultures ended up generating similar yields in the 3 reactors. Subsequently, cultures were carried out in cylindrical bioreactors where the dry biomass yield (0.538 ± 0.085 mg.mL-1) and the growth rate (0.50 d-1) were determined. The analysis using pulse amplitude modulated fluorescence (PAM) led to the determination of the following photosynthetic parameters: maximum quantum yield (0.20 ± 0.01) and effective (0.18 ± 0.004), saturating irradiance (250 μmol photons m2 s-1), maximum electron transport rate (70 μmol em- m2 s-1) and light absorption efficiency (0.27 ± 0.009 m2/mg Chl a), and from these, the theoretical rate of CO2 fixation (0.075 ± 0.008 g C/mg Chl a.day). For the biochemical composition of R. lineare, the total content of proteins (109.202 ± 0.00135 μg/mL), lipids (6.47 ± 1.29 %DW), carbohydrates (42.440 ± 3.202 μg/mL), chlorophyll a (7.96 ± 1.06 µg/mL), carotenoids (1.79 ± 0.30 µg/mL) and phycocyanin (11.201 ± 3.734 µg.mL-1). Extracts made from the biomass showed an antioxidant activity of 25% in DPPH, and no toxic effect against Artemia salina. The metabolomic analysis revealed the presence of glycerolipids, glycolipids and dephytylated chlorophyll catabolites, but did not identify toxins or compounds belonging to secondary metabolism. When compared to the main microalgae species currently commercialized for food supplementation, R. lineare stands out for presenting a higher protein content, similar contents of the other compounds and an apparent low toxicity, evidencing a potential application for the species.
Characterization of the cyanobacterium Rhabdoderma lineare: a physiological, biochemical and metabolic approach
Keywords: Toxicidade; Fotossíntese; Metabolômica; CIENCIAS BIOLOGICAS::BOTANICA::BOTANICA APLICADA